THE APPLICATION OF INQUIRY TRAINING LEARNING MODEL WITH MULTIREPRESENTATION APPROACH TOWARD LEARNING OUTCOMES AND CRITICAL THINKING SKILL IN SENIOR HIGH SCHOOL - Yunita Pakpahan; Nurliana Marpaung; Beatrik Nova (INPAFI (Inovasi Pembelajaran Fisika), 2019)
This research have purpose  knowing whether the learning outcomes and critical thinking skills of students using the inquiry training learning model are better than conventional learning in material work and energy in the class X SMAN 1 Perbaungan.This type of research is a quasi-experimental design with two group pre-test-post-test. The population in this research were all students of class X second semester SMAN 1 Perbaungan which consisted of 4 classes totaling 144 people. The research sample was taken two classes, namely class X-A2 (as experimental class) and class X-A3 (as control class) each of the 36 students was determined by simple random sampling technique. The instruments used are objective tests, namely cognitive questions form of multiple choice learning outcomes 15 questions and 5 questions of critical thinking skills in the form of descriptions. Based on the results of the reseach obtained the average value of pretest experimental class learning outcomes is 31,27 and the average value control class is 30,16 while the average value of critical thinking skills pretest experimental class is 17,44 with the average value control class is 16,89. Through testing the hypothesis test results are obtained that the initial ability of the two classes is equivalent. Then given different treatment, the experimental class with inquiry training learning model with multirepresentation approach and control class with conventional learning. Posttest data obtained is average value experimental class learning outcomes 78 and average control class 65 while the average value of critical thinking skills experimental class is 77,33 and control class 67,47. These results illustrate that inquiry learning training with multirepresentation approach is better than conventional learning in work and energy matter in class X SMAN 1 Perbaungan A.Y 2018/2019.Keyword: Inquiry training, multi representation approach, learning outcomes, critical thinking skill